Inventory Policy Control Using a Continuous Review Model Based on Information Systems: A Case Study in a Restaurant Industry - Ichsan Sarafi; Laila Nafisah; Ahmad Muhsin (OPSI, 2021)
The development of information technology has become a necessity for every company, one of which is the optimization of inventory planning. The joint warehouse owned by the Chickenpedia Restaurant which has to supply various types of raw materials to the three restaurant branches often experiences stock outs and has to make emergency orders resulting in losses. For this reason, it is necessary to control the inventory of raw materials in the shared warehouse so that stock outs can be overcome and losses that arise can be minimized. One of them is by using the Continuous Review method. By using this method, the optimal order quantity and reorder point will be obtained. The weakness is iterative calculation and monitoring of raw material stock manually. For this reason, it is necessary to support an information system to speed up and make it easier to calculate when to place an order and how many orders of raw materials to suppliers so as to reduce the occurrence of running out of raw materials. The Information System can also monitor the stock of raw materials every day in real time based on the number of incoming and outgoing goods that enter the application.